Unraveling structural transitions and kinetics along the fold-switching pathway of the RfaH C-terminal domain using exchange-based NMR - Mengli Cai; Jinfa Ying; Juan M. Lopez; Ying Huang; G. Marius Clore (Proceedings of the National Academy of Sciences, 2025)
The bacterial transcriptional regulator RfaH comprises structurally and functionally distinct N- (NTD) and C- (CTD) terminal domains. The latter switches from a helical hairpin packed against the NTD to a five-stranded β-roll upon displacement by RNA polymerase binding. Here, we use exchange-based NMR to probe fold-switching intermediates sampled by the isolated CTD. In addition to the predominant (~76 to 77%), semistable β-roll conformation (state A), we identify four structurally and kinetically distinct states: A′, B, B′, and B″. State B is NMR observable with an occupancy of ~23%, exchanges slowly (τ ex ~ 300 ms) with the major A species, and comprises a largely unfolded ensemble with transient occupancy of helical (α5*) and β-hairpin (β1*/β2*) elements. Backbone chemical shift-based structure predictions using the program CS-ROSETTA suggest that the two transient structural elements within the B state may interact with one another to form a semicompact structure. A′ (~0.35%) is an off-pathway state that exchanges rapidly (τ ex ~ 1 ms) with state A and likely entails a minor localized conformational change in the β1/β2 loop. State B′ (~0.3%) exchanges rapidly (τ ex ~ 1.2 ms) with state B and exhibits downfield 15 N backbone shifts (relative to B) in the α5* region indicative of reduced helicity. Finally state B″ (~0.05%) exchanges rapidly (τ ex ~ 0.8 to 1 ms) with either B′ (linear model) or B (branched model), displays significant differences in absolute 15 N chemical shift from states B and B′, and likely represents a further intermediate with increased helicity along the fold-switching pathway.